The Effect of Transformational Leadership Style, Work Environment, and Organizational Culture on Employee Loyalty of PT Sucofindo (Persero) Padang Branch - Reza, Muhammad; Yulihasri, Yulihasri (CV. Lenggogeni Data Publishing, 2024)
This study aims to investigate the influence of transformational leadership, work environment, and organizational culture on employee loyalty at PT Sucofindo (Persero) Padang Branch. Quantitative methods are used to analyze data collected through questionnaires distributed to company employees. The results of the analysis show that transformational leadership and work environment have a positive and significant influence on employee loyalty, with the better the application of these two factors, the higher the level of employee loyalty. However, the effect of organizational culture on employee loyalty is not statistically significant although positive. This research provides important insights for company management in understanding the factors that can increase employee loyalty, in the hope that it can provide a basis for developing more effective management strategies in maintaining a positive relationship between the company and its employees. Abstrak Penelitian ini bertujuan untuk menginvestigasi pengaruh kepemimpinan transformasional, lingkungan kerja, dan budaya organisasi terhadap loyalitas karyawan di PT. Sucofindo (Persero) Cabang Padang. Metode kuantitatif digunakan untuk menganalisis data yang dikumpulkan melalui kuesioner yang disebarkan kepada karyawan perusahaan. Hasil analisis menunjukkan bahwa kepemimpinan transformasional dan lingkungan kerja memiliki pengaruh positif dan signifikan terhadap loyalitas karyawan, dengan semakin baiknya penerapan kedua faktor tersebut, semakin tinggi tingkat loyalitas karyawan. Namun, pengaruh budaya organisasi terhadap loyalitas karyawan tidak signifikan secara statistik meskipun positif. Penelitian ini memberikan wawasan yang penting bagi manajemen perusahaan dalam memahami faktor-faktor yang dapat meningkatkan loyalitas karyawan, dengan harapan dapat memberikan dasar bagi pengembangan strategi manajemen yang lebih efektif dalam memelihara hubungan positif antara perusahaan dan karyawannya. Kata Kunci: Kepemimpinan transformasional, Lingkungan kerja, Budaya organisasi, Loyalitas karyawan